THE IMPACT OF MOBILE TRADING ADOPTION ON FINANCIAL PERFORMANCE AND MARKET VALUATION: EVIDENCE FROM DAR ES SALAAM STOCK EXCHANGE PLC (2018–2024) - Issa Ahmed; Ramadhan Hussein Kagwandi; Hamisa Rashid Kuffa; Peace Faustine (Jurnal Akuntansi dan Ekonomi Bisnis, 2026)
This study assesses whether Dar es Salaam Stock Exchange PLC’s adoption and scaling of the Mobile Trading Platform (“Hisa Kiganjani”) coincided with changes in accounting-based financial performance and market valuation. Using a paired pre–post design, it compares 2017–2020 (pre) with 2022–2025 (post), excluding 2021 as a transition year. Five ratios (CR, ROA, DAR, DER, TATO) are combined into a standardized composite Financial Performance (FP) index, and year-end closing price is used as a proxy for market valuation. With four matched pairs, Wilcoxon signed-rank tests indicate no statistically significant shift in the FP index (W = 2.0, p = 0.375) and a directional but statistically non-significant increase in share price (W = 0.0, p = 0.125). Descriptively, 2025 shows increased mobile participation and turnover alongside trading-rule reforms. Overall results suggest an indicative pattern consistent with a gradual absorption interpretation, where valuation effects strengthen as adoption scales and market design improves, while accounting ratios show no discrete change.